HUBUNGAN PERSEPSI TERHADAP IKLIM KELAS DENGAN MINAT BELAJAR FISIKA SISWA KELAS XI IPA SMA SE-KECAMATAN TUALANG - Elfrida Nella Sari Nella Sari; Mitri Irianti Irianti; Zuhdi Ma’aruf Ma’aruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the relationship between perceptions of classroom climate with interesting in learning physics. The samples in this study come from the population eleventh grade of science high school Se-District of Tualang. This research technique using proportionate cluster random sampling that is used when the population consists of groups or individuals. Data collection methods used in this studying using a instrument of class perceptions of climate and interest in learning physics. The data obtained were further analyzed using pearson product moment corelation technique. Data analysis conducted shows that there is relationship between the perception of the class climate interest physics to learn. This is shown by the magnitude of the correlation coefficient (r) variable 0,75 and thitung> ttabelvariable 4,059>1,67. This results of this study stated that the hypothesis is high category, interest in learning physics variable (2,73) and perception of the class climate variable (2,82). There is relationship between perceptions of classroom climate and interest in learning physics Key Words:Perceptions of ClassClimate, Interest in LearningPhysics